Preliminary experience in the arthroscopically assisted treatment of tibial plateau fractures: Arthroscopically assisted reduction - Quattrini, Fabrizio; Ciatti, Corrado; Strigini, Giacomo; Maniscalco, Pietro (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the study: Fractures involving the tibial plateau make up 1% of all fractures. Treatment can take advantage of various techniques, including arthroscopically assisted surgical reduction. This procedure is certainly viable for Schatzker III fractures and, in some cases, for Schatzker II. The use of the arthroscope makes possible a smooth reduction of the fractured bone, decreasing the risk of post-traumatic osteoarthritis, and also allows to diagnose and, if necessary, also treat the associated intra-articular lesions, which often are not highlighted during the classical preoperative investigations. Methods: In the last year we have operated with this technique 8 of the 22 cases of fracture of the tibial plate that have come to our emergency Department. Using the Schaztker classification, we performed an arthroscopically assisted reduction to treat type II and III fractures. The surgical operations involved a first arthroscopic phase, to assess intrarticular damage (bone, cartilage, ACL, PCL, menisci), a second phase for possible treatment of intrarticular lesions and reduction of fractures under arthroscope or open osteosinthesis. Finally, a last arthroscopic check was performed. Results: We obtained excellent results, as we were able to always have a fracture reduction of less than 1 mm, while clinically all the patients could have an early and almost complete functional recovery after only 2 months. Conclusion: The arthroscopically assisted technique could be an effective way to adress the anatomical reduction of tibial plate fractures, but must only be used in the indicated cases.